Jurnalisme Infotainment Dalam Perspektif Etika Komunikasi Islam (Study Analisis Pada Tayangan Brownis Trans Tv - Riko Saputra (Tabayyun: Journal of Journalism, 2023)
Abstrak This thesis is entitled “Infotainment Journalism in the Perspective of Islamic Communication Ethics (Study Analysis on Brownis Trans TV Shows). The problem raised from this research is how Infotainment Journalism in Trans TV Street Brownis Shows, how Infotainment Journalism in Trans TV Street Brownis Shows according to Islamic Communication Ethics. This type of research is qualitative, the main or primary sources are YouTube channels, live broadcasts and websites. Data collection techniques through observation and documentation and use the theory of content analysis. Data collection of most television shows The rapid digitalization in recent years has made television (TV) in Indonesia increasingly abandoned. In this research, the Brownis Jalan-Jalan infotainment provides various types of segment content ranging from social, cultural, economic, and entertainment, even with comedy nuances, adding an impression of interest to the audience who watches to entertain and educate at the same time the life experienced by people in his daily life is depicted in the Brownis Jalan Jalan (BJJ) segment. Islamic communication agrees with Jalaluddin Rakhmat who said that there are six forms of discourse (Qawlan), qawlan is someone's speech or words when communicating between humans which is understood in the Qur'an. The researcher placed qawlan in his research in the form of Qawlan Sadidan, Qawlan Baligha, Qawlan Karima, Qawlan Ma'rufan, Qawlan Layyina, and Qawlan Maysura. Keywords : Journalism, Infotainment, Analysis